Hybrid intumescent coatings for wood protection against fire action - Canosa, Guadalupe (2011)
Hybrid intumescent coatings for wood protection against fire were developed. Several resins were chosen as film-forming materials. Similar active and complementary pigments were used. To improve the efficiency, coatings were formulated by using reinforcing fibers. The performance of hybrid coatings was determined on panels of Araucaria angustifolia; some coatings showed an excellent performance in thermal conductivity test, two-foot tunnel, OI cabin, UL 94 horizontal-vertical chamber, and TGA trials. The best performance was achieved with chlorinated rubber, followed by phenolic resin, and finally by epoxy resin. With respect to fibers, hybrid formulations had a superior performance in relation to the respective reference samples; in addition, coatings displayed the best behavior with alumina, carbon, aramid, and glass fibers in their composition, in that order. An elevated synergistic effect was observed; the mentioned synergistic effect could be based on that the nature of the interface in a composite would affect its combustibility.